[(Z)-N-(3-Fluorophenyl)-O-methylthiocarbamato-κS](triphenylphosphane-κP)gold(I): crystal structure, Hirshfeld surface analysis and computational study - Yeo, Chien Ing *; Tan, Sang Loon *; Kwong, Huey Chong *; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The title phosphanegold(I) thiolate, C26H22AuFNOPS or [Au(C8H7FNOS)(C18H15P)], has the AuI centre coordinated by phosphane-P [2.2494 (8) A ˚ ] and thiolate-S [2.3007 (8) A ˚ ] atoms to deﬁne a close to linear geometry [P—Au—S = 176.10 (3)⁰]. The thiolate ligand is orientated so that the methoxy-O atom is directed towards the Au atom, forming an Au...O close contact of 2.986 (2) A ˚ . In the crystal, a variety of intermolecular contacts are discerned with ﬂuorobenzene-C—H...O(methoxy) and phenyl-C—H...F interactions leading to dimeric aggregates. These are assembled into a three-dimensional architecture by phenyl-C—H...S(thiolate) and phenyl-C—H...π(ﬂuorobenzene, phenyl) interactions. Accordingly, the analysis of the calculated Hirshfeld surface shows 30.8% of all contacts are of the type C...H/H...C but this is less than the H...H contacts, at 44.9%. Other signiﬁcant contributions to the surface come from H...F/F...H [8.1%], H...S/S...H [6.9%] and H...O/ O...H [3.2%] contacts. Two major stabilization energies have contributions from the phenyl-C—H...π(ﬂuorobenzene) and ﬂuorobenzene-C— H...C(imine) interactions (-37.2 kcal mol-1), and from the ﬂuorobenzene C—H...F and phenyl-C—H...O interactions (-34.9 kcal mol-1), the latter leading to the dimeric aggregate.